The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ijms21239208
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Prion Protein: A Promising Therapeutic Target for Cancer

Abstract: Studies on the cellular prion protein (PrPC) have been actively conducted because misfolded PrPC is known to cause transmissible spongiform encephalopathies or prion disease. PrPC is a glycophosphatidylinositol-anchored cell surface glycoprotein that has been reported to affect several cellular functions such as stress protection, cellular differentiation, mitochondrial homeostasis, circadian rhythm, myelin homeostasis, and immune modulation. Recently, it has also been reported that PrPC mediates tumor progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 109 publications
1
29
0
Order By: Relevance
“…The general functions of PrP C have been extensively investigated via gene knockout experiments. The putative functions associated with PrP C ( Figure 2 A) include the stress response [ 33 , 34 , 35 , 36 ], providing protective effects against oxidative stress [ 37 , 38 , 39 ], cellular differentiation [ 40 , 41 , 42 ], neuronal excitability [ 43 , 44 , 45 ], myelin maintenance [ 46 , 47 , 48 ], circadian rhythm [ 49 , 50 ], metal ion homeostasis [ 51 , 52 , 53 ], modulation of the immune system [ 54 ], the regulation of amyloid beta and tau protein [ 55 ], control of the cellular signaling pathways [ 56 , 57 ], and a few other common cellular processes [ 7 ]. Since PrP C downregulation occurs during the disease incubation period [ 58 ], the loss of normal PrP C function may partly underlie the pathology of prion protein-related diseases, and PrP C could be targeted for therapeutic purposes.…”
Section: General Characteristics Of Cellular Prion Proteins In Kidneysmentioning
confidence: 99%
See 2 more Smart Citations
“…The general functions of PrP C have been extensively investigated via gene knockout experiments. The putative functions associated with PrP C ( Figure 2 A) include the stress response [ 33 , 34 , 35 , 36 ], providing protective effects against oxidative stress [ 37 , 38 , 39 ], cellular differentiation [ 40 , 41 , 42 ], neuronal excitability [ 43 , 44 , 45 ], myelin maintenance [ 46 , 47 , 48 ], circadian rhythm [ 49 , 50 ], metal ion homeostasis [ 51 , 52 , 53 ], modulation of the immune system [ 54 ], the regulation of amyloid beta and tau protein [ 55 ], control of the cellular signaling pathways [ 56 , 57 ], and a few other common cellular processes [ 7 ]. Since PrP C downregulation occurs during the disease incubation period [ 58 ], the loss of normal PrP C function may partly underlie the pathology of prion protein-related diseases, and PrP C could be targeted for therapeutic purposes.…”
Section: General Characteristics Of Cellular Prion Proteins In Kidneysmentioning
confidence: 99%
“…PrP C -expressing renal adenocarcinoma cells (ACHN cells) demonstrated a modest but statistically significant increase in cell viability compared with the control group via the suppression of TNF-α-induced cell death, and the PrP C expression in ACHN led to a higher proliferative index [ 125 ]. This is interesting, because there is a large volume of research on how PrP C could mediate the tumorigenic effects and promote cancer proliferation, metastasis, drug resistance, and the cancer stem cell phenotype [ 34 ].…”
Section: Prp C and Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The cellular prion protein (PrP C ) is a glycophosphatidylinositol-anchored cell surface protein that is associated with diverse cellular functions, including stress protection and cellular differentiation [ 26 ]. Recently, several studies have shown that PrP C is highly expressed in various types of cancers, including gastric [ 27 ], pancreatic [ 28 ], breast cancers, and CRC [ 29 , 30 ]. Furthermore, it has been reported that PrP C promotes cancer progression by enhancing cancer cell proliferation, metastasis, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that PrP C promotes cancer progression by enhancing cancer cell proliferation, metastasis, and drug resistance. These results suggest that PrP C is a promising therapeutic target for cancer [ 29 , 30 ]. In this study, we hypothesized that an efficient targeted DDS could be developed for CRC treatment by targeting PrP C .…”
Section: Introductionmentioning
confidence: 99%